Internationalization from a Dialogical Perspective: A Responsibility of the Federal Network of Professional, Scientific and Technological Education - Samuel de Carvalho Lima (Instituto Federal de Educação, Ciência e Tecnologia do Rio Grande do Norte, 2021)
This paper aims to characterize internationalization as a responsibility of the Federal Network of Professional, Scientific and Technological Education. My theoretical assumptions are based on the concept of dialogical subject, the Brazilian conceptual basis for Professional Education, and internationalization as a complex and changing process. My methodological choices led me to do an interpretative dialogical analysis of IFRN institutional documents, highlighting how they characterize internationalization. My analysis makes a claim for internationalization interrelating it with integral education, research, extension, management, the capillaries of the federal network, and social impact.